Saving and Uncertainty: The Precautionary Demand for Saving - Leland, Hayne E. (Quarterly Journal of Economics, 1968)
I. Introduction, 465. — II. A two period model of consumption, 466. — III. The effect of uncertainty on saving, 467. — IV. Decreasing risk aversion and precautionary saving, 468. — V. Speculations on the consumption function, 470. — VI. Conclusion, 472.